PENINGKATAN MINAT BACA AL-QUR’AN MELALUI STRATEGI KOMUNIKASI PERSUASIF - Muhammad Randicha Hamandia; Zhila Jannati, Iin Karlina (Program Studi Komunikasi dan Penyiaran Islam UIN Raden Fatah Palembang, 2022)
The purpose of this study was to find out how to increase youth reading interest in the Koran through persuasive communication strategies of the Al-Irsyad Mosque Youth Association (IRMA) Board. This type of research is field research with a qualitative approach and analyzed with descriptive qualitative. The data collection techniques that the researchers used in this study were observation, interviews and documentation. Data analysis techniques are data reduction, data display and drawing conclusions. The research results of Irma's members used a persuasive communication strategy covering three stages, namely strategy formulation, implementation, and strategy evaluation.